2007
DOI: 10.1071/fp07175
|View full text |Cite
|
Sign up to set email alerts
|

Boron uptake by the root cortex symplast of tomato and pea plants: evidence for low-boron-induced active transport

Abstract: The objective of this research was to test the hypothesis of the existence of an active boron (B) uptake into the cortical cells induced by low B supply. The uptake of B was characterised in two tomato (Lycopersicon esculentum Mill.) genotypes: B-efficient FER and B-inefficient mutant T3238. In addition, pea (Pisum sativum L.) was used as an anatomically appropriate model for obtaining intact root cortex. Time course uptake studies in tomato indicate that the B-inefficient mutant was defective by the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Plant roots were able to concentrate boron 2.7-fold compared to the external nutrient solution indicating the existence of a B-concentrating mechanism located in root cortex cells, xylem parenchyma cells of the stele, or both, according to previous reports (Takano et al, 2008). Active transport of boron, induced by low external boron concentration, has been recently shown for tomato (Savic et al, 2007) in which B was concentrated up to 4-fold in the cell sap of the root cortex compared to the external solution (0.5 lM). However, the concentrating mechanism showed a saturable uptake pattern, similarly to other studies, which resulted in a lower concentration factor at higher external concentrations (ca.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Plant roots were able to concentrate boron 2.7-fold compared to the external nutrient solution indicating the existence of a B-concentrating mechanism located in root cortex cells, xylem parenchyma cells of the stele, or both, according to previous reports (Takano et al, 2008). Active transport of boron, induced by low external boron concentration, has been recently shown for tomato (Savic et al, 2007) in which B was concentrated up to 4-fold in the cell sap of the root cortex compared to the external solution (0.5 lM). However, the concentrating mechanism showed a saturable uptake pattern, similarly to other studies, which resulted in a lower concentration factor at higher external concentrations (ca.…”
Section: Discussionsupporting
confidence: 58%
“…Bellaloui and Brown (1998) reported that a low-B-tolerant tomato cultivar was more capable of translocating B from roots to leaf tissues resulting in higher B content in the aerial parts compared to a low-B-sensitive cultivar. A tomato B-efficient cultivar also showed enhanced B uptake by the root cortex cells based on low-B-induced active transport (Savic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In tomato (Lycopersicon esculentum), early studies using two genotypes showed that the B-inefficient genotype T3238 has a defect in xylem loading compared to the B-efficient genotype FER [43,44]. In addition, a recent study using these genotypes revealed that the B-efficient genotype FER showed B accumulation in the root cell sap at concentrations higher than in the external medium when precultured with a low B supply (0.5 mM), whereas the B-inefficient genotype T3238 did not [45]. Low-B-inducible accumulation of B in root cell sap and xylem sap was also described in sunflower plants [33,34].…”
Section: Reviewmentioning
confidence: 94%
“…However, accumulation of B was also observed in cortical cells of pea (Pisum sativum), which does not develop exodermal cells. The B concentration in pea root cortical cell sap was tenfold higher than in the external medium under conditions of low B supply (0.5 mM), but was similar with adequate B supply (10 mM) [45]. As-yet-unknown B importers might transport B against concentration gradients across plasma membranes in some plant species.…”
Section: Reviewmentioning
confidence: 99%
“…Widespread opinion that B uptake by plant roots is mainly passive process at sufficient supply as well as different mechanisms proposed for low supply, including active uptake by root cortex cells as shown for pea and tomato (Savić et al, 2007) should be also taken under consideration. Sunflower was also often used in studies on B uptake, xylem loading and compartmentation.…”
Section: Resultsmentioning
confidence: 99%